Konstruksi Identitas Kebangsaan Ganda Diaspora Tionghoa Indonesia Melalui Penggunaan Bahasa - Sidarta, Yos (Universitas Terbuka, 2023)
National identity is constructed by primordial, sacred, character and economic factors. Indonesia as a multi-ethnic country, the population consists of various ethnic groups and diaspora such as the Chinese, Arab and Indian diaspora. As an independent and sovereign nation, even though there are many tribes and there is also a diaspora, Indonesia's national identity can be recognized by other nations in the world, one of which is through language. The Chinese diaspora is the diaspora with the largest number in Indonesia, after becoming Indonesian citizens they also still have a Chinese national identity considering the history of their ancestors from mainland China. Then when they live in Indonesia and become Indonesian citizens, they use Indonesian as the language of social communication and have an Indonesian national identity. However, their Chinese national identity is still attached. The condition of the formation of a dual national identity in the Chinese diaspora through the use of Chinese and Indonesian languages ​​raises the question, what is their real national identity? Then what social consequences arise as a result of the dual national identity. The purpose of this article is to understand the influence of language on the formation of dual national identity and its consequences. The research method is based on literature study and qualitative data from interviews with several Chinese diaspora families based on their life experiences when they were still in Indonesia. Keywords: Chinese Diaspora ; Language and Dialect ; National Identity